PENGARUH KUALITAS SUMBER DAYA MANUSIA, DISIPLIN KERJA, DAN PENGEMBANGAN KARIR TEHADAP PRESTASI KERJA PEGAWAI DINAS PERHUBUNGAN PROVINSI MALUKU - Ferdy Leuhery (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2018)
The quality of human resources is an important factor that can support the success of an organization, to achieve the goal to achieve. Want a pullback of an organization depend largely on the quality of human resources, to improve the performance of existing employees in the instani. To raise the achievements of the work of employees, there are factors that are necessary in instances, these factors include the increased discipline employees and provides an opportunity to develop a career employee, thus passing all that any employee accomplishments can ditigkatkan. This research aims to examine and analyze the pegaruh quality of human resources, career development and Discipline against the achievements of the work of employees. The research method used is the quantitative methods of research i.e. research survey to describe the relationships between variables and explanatory research is to explain the relationship between variables through testing The hypothesis. Analysis of the test tools used in this enelitian that is by using multiple regression.The hypothesis was tested with the test method F, t-test, and the coefficient of determination (R2), research results show that (1) the quality of HR positive effect towards the Accomplishment of work, (2) the work of influential positive Discipline against the work achievement, (3) career development a positive effect against Department Employees work achievement of transportation Province of Maluku. Keywords: Quality Of Human Resources, Career Development, Work Discipline, Work Achievement.